2022
DOI: 10.1038/s41563-022-01209-1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling structural evolution and oxygen-redox electrochemistry in layered transition metal oxides

Abstract: Lattice oxygen redox activity offers an unexplored way to access the latent superior electrochemical property of transition metal oxides for rechargeable batteries. However, the redox reaction of the lattice oxygen is often accompanied by unfavorable structural transformations and the corresponding degradation of electrochemical performances, precluding its practical application. Herein, we explore the close interplay between the local structural change during the dynamic intercalation process and the solid-st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 67 publications
4
92
3
Order By: Relevance
“…The specific electrochemical performance of GO/TMOs could be attributed to the distinct oxygen stabilization mechanisms of the TMOs. According to the report by Eum et al 53 the oxidized oxygen in the lattice can be at one of the three states: non-stabilized oxygen, π-stabilized oxygen or σ-stabilized oxygen. π-Stabilization occurred between the oxygen and neighbouring transition metals in the layered structure, while σ-stabilization was promoted when transition metal–oxygen decoordinated.…”
Section: Resultsmentioning
confidence: 99%
“…The specific electrochemical performance of GO/TMOs could be attributed to the distinct oxygen stabilization mechanisms of the TMOs. According to the report by Eum et al 53 the oxidized oxygen in the lattice can be at one of the three states: non-stabilized oxygen, π-stabilized oxygen or σ-stabilized oxygen. π-Stabilization occurred between the oxygen and neighbouring transition metals in the layered structure, while σ-stabilization was promoted when transition metal–oxygen decoordinated.…”
Section: Resultsmentioning
confidence: 99%
“…Voltage hysteresis is intractable and widely exists in ARR systems, which not only penalizes energy density but also is detrimental to cycling performance. , The relationship between voltage hysteresis and ARR is under debate. , Nowadays, it is widely accepted that the lattice distortion and formation/cleavage of O-O dimers like (O 2 ) 2– /(O 2 ) − /O 2 are the origin of voltage hysteresis in ARR systems. In addition, the migration of cations and phase transitions can degrade the voltage hysteresis . Recently, it was revealed that an ordered superstructure plays an important role to eliminate voltage hysteresis by alleviating cation migration and oxygen dimerization.…”
Section: Challenges Of Arr In Sibsmentioning
confidence: 99%
“…Sodium-ion batteries (SIBs) have many advantages in large-scale energy storage applications due to the similar working principles as lithium-ion batteries (LIBs) and abundant sodium resources. Layered transition metal oxide materials, such as Na x MO y (M = Mn, Co, Ni, Fe, Cr, etc. ), have advantages as electrode materials of SIBs, including the high specific capacities, simple structure, low cost, and simple synthesis. However, the voltage profile of Na x MO y experiences a large hysteresis because of the structural changes during the charge/discharge process.…”
Section: Introductionmentioning
confidence: 99%